The moral values in Aladdin (2019) - Nur Wahyu Puspitasari; Adip Arifin; Ratri Harida (Concept : Community Concern for English Pedagogy and Teaching, 2021)
Moral values are values that relate to good and bad deeds which guide people's life in a positive wayy. In practice, moral values function to motivate society members to act well. This present study aimed at exploring the moral values in Aladdin movie; a musical fantasy movie released in 2019. The movie is directed by Guy Ritchie, an English film director, producer and also businessman. The researchers employed descriptive qualitative method and designed it as the research design. The source of the data in this study was the dialogue among the characters in Aladdin movie. Documentation was used as the technique to collect the data. Besides the researchers as the instrument, another instrument used was documentation sheet. To analyse the data, the researchers used descriptive analysis. The results of the study showed that there were a number of moral values found in Aladdin film, including courage, honesty, self-confidence and capability, being helpful, love and affection, respect, loyalty, fairness and humanity, and kindness. These findings also indicate that honesty is the most dominant moral value displayed throughout the film scene. Particularly, it appears three fourteen times in different dialogue and actions. Keywords: Moral Values; Aladdin Movie; Literary Study